Pengembangan Sejarah Lokal sebagai Sumber Pembelajaran Sejarah yang Kontekstual - Erlina Wiyanarti; Nana Supriatna; Murdiyah Winarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
The history learning’s vision is the value that inculcation to students in order to form perfect character. However, in practice, history subject that included in the national curriculum limited to national aspects and teachers ability sometimes perceived to be less relevant to time demand. This article will discuss the potential of developing local history material as a contextual source of learning in addition to national history based on a descriptive study of the Community Service Program in 2019. Through literature study, we can conclude that (1) local history has strategic value as an alternative source of history learning (2) the use of local history as a source of contextual history learning can be integrated with national history learning (3) the lack of use of local history in learning in schools requires a structured effort to develop it optimally.